ANALISIS EFISIENSI PEMASARAN UBI JALAR DI KABUPATEN LAMPUNG TENGAH - Angginesa Pradika; Ali Ibrahim Hasyim; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
The purpose of this study was to analyze the efficiency of the marketing of sweet potato in Central Lampungregency. The method used in this research was the analysis of the model of S-C-P (structure, conduct, andperformance). The S-C-P model is used to analyze an organization's market. The results showed that thesweet potato marketing systems in Central Lampung regency was inefficient, because the first structure ofthe market (market structure) was formed oligopsoni, both the behavior of the market (market conduct)farmers, which was done a cash payment system and through the bargaining process, variability thirdmarket (market performance), and there were four sweet potato marketing channels. The marketing marginsand the fourth and Profit margin Ratio (RPM) was not evenly spread, and the price transmission elasticity(Et) was worth 0.69 (Et <1). The means of the market competition was not run perfectly, but the share in theproducer marketing channels in Central Lampung farmers was high as 70.54 percent. It meant that thehigher the share of producers would be the more efficient marketing.